Peran Guru PAI Dalam Kegiatan Evaluasi Pembelajaran - Zulfa Iftinani Muchtar; Muhammad Zidan Nur Ihsan; Nur Raihanah Amani (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
In Islamic religious education learning activities, the role of a PAI (Islamic Religious Education) teacher is very important in evaluation activities. Because in evaluation activities, an Islamic religious education teacher can find out whether his students have achieved what is expected or not. In addition to determining student graduation, evaluation activities are useful for evaluating learning methods or strategies. This article aims to determine the role of PAI teachers in evaluation activities and the obstacles faced by PAI teachers in evaluation activities. This research is based on field research. This article uses a phenomenological approach that raises a phenomenon in one of the vocational schools in Klaten. The results of this study show that the role of PAI teachers in evaluation activities is very important and crucial. This is because a teacher as an evaluation subject plays a role in the evaluation process, so that students can achieve learner’s goals. Keywords: Islamic Education Teacher, Evaluation, Learning.